Endoscopic ultrasound‐guided versus endoscopic retrograde cholangiopancreatography‐guided biliary drainage for primary treatment of distal malignant biliary obstruction: A systematic review and meta‐analysis. Issue 1 (6th July 2019) - Jin, Zheng; Wei, Yaping; Lin, Huapeng; Yang, Jing; Jin, Hangbin; Shen, Sisi; Zhang, Xiaofeng
Abstract : Objectives: Current evidence supporting the utility of endoscopic ultrasound‐guided biliary drainage (EUS‐BD) as primary treatment for distal malignant biliary obstruction (MBO) is limited. We conducted a meta‐analysis to compare the performance of EUS‐BD and endoscopic retrograde cholangiopancreatography‐guided biliary drainage (ERCP‐BD) as primary palliation of distal MBO. Methods: We searched several databases for comparative studies evaluating EUS‐BD vs. ERCP‐BD in primary drainage of distal MBO up to 28 February 2019. Primary outcomes were technical success and clinical success. Secondary outcomes included adverse events, stent patency, stent dysfunction, tumor in/overgrowth, reinterventions, procedure duration, and overall survival. Results: Four studies involving 302 patients were qualified for the final analysis. There was no difference in technical success (risk ratio [RR] 1.00; 95% confidence interval [95% CI] 0.93–1.08), clinical success (RR 1.00; 95% CI 0.94–1.06) and total adverse events (RR 0.68; 95% CI: 0.31–1.48) between the two procedures. EUS‐BD was associated with lower rates of post‐procedure pancreatitis (RR 0.12; 95% CI 0.02–0.62), stent dysfunction (RR 0.54; 95% CI 0.32–0.91), and tumor in/overgrowth (RR 0.22; 95% CI 0.07–0.76). No differences were noted in reinterventions (RR 0.59; 95% CI 0.21–1.69), procedure duration (weighted mean difference −2.11; 95% CI −9.51 to 5.29), stent patency (hazard ratio [HR] 0.61; 95% CI 0.34–1.11), and overall survival (HR 1.00; 95% CI 0.66–1.51). Conclusions: With adequate endoscopy expertise, EUS‐BD could show similar efficacy and safety when compared with ERCP‐BD for primary palliation of distal MBO and exhibits several clinical advantages.